ANALISIS FEMINISME DALAM PENINGKATAN KEJAHATAN OLEH PEREMPUAN DI AMERIKA SERIKAT PERIODE 2000-2022 - Andana Tedja Martana Prianto (Journal of International Relations, 2023)
The impact of the feminist movement has led to an augmentation in the labor market participation of women globally. Discussions surrounding gender equality and women's welfare have been elevated as a result of the increasing prominence of feminism. Nevertheless, the upsurge of women's roles also extends to criminal activity. While men still dominate the realm of crime, there has been a significant rise in crimes perpetrated by women in contrast to a decreasing trend among men. Thus, the objective of this investigation is to elucidate the reason behind the escalation in criminal activity committed by women. Drawing on the theory of Marxist feminism, the author examines the intersection between capitalism and the patriarchal system in perpetuating the oppression of women. Using an empirical feminist method, the study focuses on sex and drug trafficking from 2000-2020. The results reveal persistent gender inequality, exemplified by lower wages for women and the hurdles they face in career advancement, which may drive some women to commit crimes.